2020
DOI: 10.1002/jcph.1743
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Phenobarbital in Neonates and Infants on Extracorporeal Membrane Oxygenation and the Influence of Concomitant Renal Replacement Therapy

Abstract: The objective of this study was to describe the pharmacokinetics (PK) of intravenous phenobarbital in neonates and infants on extracorporeal membrane oxygenation (ECMO) and to provide dosing recommendations in this population. We performed a retrospective single‐center PK study of phenobarbital in neonates and infants on ECMO between January 1, 2014, and December 31, 2018. We developed a population PK model using nonlinear mixed‐effects modeling, performed simulations using the final PK parameters, and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Conversely, Thibault et al reported the increasing effect of ECMO therapy on phenobarbital Vd, but no effect on CL [36]. In another larger group of patients, the same research group found no effect of ECMO on Vd, but reported a 6-fold increase of phenobarbital CL in patients undergoing CVVHDF compared to the patients without CVVHDF [50]. Given the small number of patients included in these analyses, larger studies are needed to elucidate the pharmacokinetic changes induced by ECMO to recommend phenobarbital dosing in this specific clinical setting.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, Thibault et al reported the increasing effect of ECMO therapy on phenobarbital Vd, but no effect on CL [36]. In another larger group of patients, the same research group found no effect of ECMO on Vd, but reported a 6-fold increase of phenobarbital CL in patients undergoing CVVHDF compared to the patients without CVVHDF [50]. Given the small number of patients included in these analyses, larger studies are needed to elucidate the pharmacokinetic changes induced by ECMO to recommend phenobarbital dosing in this specific clinical setting.…”
Section: Discussionmentioning
confidence: 95%
“…Urea level was not found to be a significant covariate for the phenobarbital CL. Additionally, creatinine was also not found to be a significant descriptor of the phenobarbital CL variability [33,45,50], while Moffett et al described a relationship between serum creatinine and phenobarbital CL [39]. As inflammation can influence CYP450 enzyme activity, the C-reactive protein (CRP) level was also tested as a predictor of phenobarbital CL in the critically-ill neonates undergoing ECMO (47), but no relation was found.…”
Section: Laboratory Parametersmentioning
confidence: 99%
“…Previous clinical trials comparing newborns and infants following PB administration have revealed differences in the characteristics between the two development stages [ 3 , 4 ]. For pediatric patients, specifically for newborns, infants, toddlers, and preschoolers, organ and body development can make a big difference in one year.…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital (PB) was approved as a treatment for epileptic seizures in 1912; it remains a first-line drug for treating neonatal seizures even more than 100 years after its approval [ 1 , 2 ]. Therefore, multiple studies have investigated PB administration in pediatric patients [ 3 , 4 ]. PB exerts its effect through the enhancement of GABA-ergic inhibition and reduction of glutamatergic excitation via inhibition of AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This failure in response may be partially explained by the effects of ECMO on medication pharmacokinetics (31). The ECMO-related larger volume of distribution (i.e., from blood/fluid boluses circuit volume) may contribute to hemodilution and in turn to subtherapeutic antiseizure medication concentration may contribute to these issues (32, 33). Additionally, hemodynamic instability during ECMO may affect liver perfusion, thereby limiting drug metabolism (33).…”
Section: Discussionmentioning
confidence: 99%